Inwestycje w zakresie ochrony środowiska i gospodarki wodnej w powiatach ziemskich podregionu wrocławskiego - wybrane problemy - Szymańska, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper presents the problems of water and waste water management in powiats of wrocławski subregion. It shows the structure of financial outlays for environment protection and water economy and changes in it between 2000 and 2004. The paper focuses on the most important effects obtained in environment protection and water economy in powiats of wrocławski subregion. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 106-112